2017
DOI: 10.1177/0269215517719952
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus non-operative treatment for lumbar disc herniation: a systematic review and meta-analysis

Abstract: Low-quality evidence suggested that surgical treatment is more effective than non-operative treatment in improving physical functions; no significant difference was observed in adverse events. No firm recommendation can be made due to instability of the summarized data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
72
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 26 publications
(79 reference statements)
0
72
1
1
Order By: Relevance
“…10,27,40 Several studies have focused on patient-reported outcomes (PROs) as metrics of patient satisfaction. 9,43,44 Surveys like the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) were developed to objectify patient satisfaction, but that instrument's 29 questions target broader patient experiences that lack applicability to surgical specialties. 14 In their article on the evolution of HCAHPS in spine surgery, Malpani et al concluded that the metric links hospital remuneration to patient satisfaction.…”
mentioning
confidence: 99%
“…10,27,40 Several studies have focused on patient-reported outcomes (PROs) as metrics of patient satisfaction. 9,43,44 Surveys like the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) were developed to objectify patient satisfaction, but that instrument's 29 questions target broader patient experiences that lack applicability to surgical specialties. 14 In their article on the evolution of HCAHPS in spine surgery, Malpani et al concluded that the metric links hospital remuneration to patient satisfaction.…”
mentioning
confidence: 99%
“…[ 1 , 2 ] About 80% of the patients suffered from sciatica caused by LDH, which imposes heavy burden on society, families, and individuals. [ 3 , 4 ] In these cases, 10% to 20% of the patients received conservative treatment, but the pain continued, and surgery should be considered. [ 5 ] Compared with open lumbar microdiscectomy, percutaneous endoscopic lumbar discectomy (PELD) has the advantages of remarkable preservation of paravertebral structures, less bleeding, shorter operation time, and fewer complications, it is a common method for the treatment of LDH.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar disc herniation is the most common diagnosis among degenerative disorders of the lumbar spine, affecting 2 to 3% of the population, and is the main cause of spinal surgery in the adult population [1][2][3]. Wiltse et al [4] reported that the lateral lumbar spinal canal can be subdivided into three regions: the subarticular (lateral recess), foraminal (pedicle), and extraforaminal (far lateral) zone.…”
Section: Introductionmentioning
confidence: 99%